Simulation analysis and experimental study on cylinder grading of maize seeds based on discrete element method: A study on cylindrical grading of maize seeds - Minji Liu; Jiannan Wang; Zhaoyan You; Chenyang Sun; Ni Wang; Jianchun Yan; Hai Wei; Huijuan Zhang; Huanxiong Xie (PLoS ONE, 2025)
A cylindrical grader is an important piece of equipment used to grade maize seeds. However, the motion and distribution patterns of seeds within the cylindrical grading process remain poorly understood, leading to a heavy reliance on empirical adjustments of operational parameters during grading. This results in issues such as low grading efficiency, unstable operational performance, and failure to meet practical production requirements. To investigate the motion and distribution patterns of maize seeds during cylindrical grading, key simulation parameters characterizing the maize seeds and grading cylinders were experimentally determined. Discrete element models of maize seeds and the grading cylinder were subsequently developed using EDEM 2018 software. Variations in seed motion velocity and the coefficient of variation (CV) along the circumferential and axial directions were analyzed under different operational parameters, including cylinder rotational speed, inclination angle, and feeding rate. Discrete element simulations combined with orthogonal experiments revealed that the order of influence of these factors on the grading qualification rate was as follows: inclination angle > rotational speed > feeding rate. The results of the interaction analysis showed that the interaction between the inclination angle and rotational speed significantly affected the grading qualification rate, while the interactions among the other factors had no significant effect. The optimized parameter combination was identified as a rotational speed of 47.08 r/min, an inclination angle of 0.52°‌, and a feeding rate of ‌303.07 g/s‌, achieving a theoretical grading qualification rate of 97.24%. Validation experiments conducted with this optimal combination yielded a practical grading qualification rate of ‌93.83%‌, with the relative error between the experimental and predicted values below 4%‌. These results confirm the validity of discrete element simulations for analyzing maize seed motion dynamics and provide a valuable reference for further research in this field.